PENGARUH PERILAKU KONSUMTIF DAN LIFESTYLE TERHADAP MINAT PEMBELIAN PRODUK FASHION MELALUI E-COMMERCE TIKTOKSHOP - Syaifuddin Fahmi; Anton ferry Ananda; Luluk Fitriah (Juremi: Jurnal Riset Ekonomi, 2024)
This research discusses purchasing interest in fashion products at Tiktokshop. The study in this research was on students at STIE Kertanegara Malang, East Java. In this research, the sample was taken using non-probability sampling, with a purposive sampling technique. The number of samples in this research was 103 respondents. The analytical tool used is multiple linear regression using the SPSS program. The research results obtained from the t test results show that consumer behavior and lifestyle influence interest in buying fashion products at Tiktokshop. Meanwhile, the results of the F test together, both consumer behavior and lifestyle, influence interest in buying fashion products at Tiktokshop. The coefficient of determination seen in the adjusted R-squared value is 0.145 or consumer behavior and lifestyle influence the decision to purchase preloved clothing by 14.5%. It is hoped that the results of this research can be used as a reference for fashion business people in Tiktokshop who are starting to do business or who are currently doing business